A study of allergic responses of formaldehyde in first year MBBS students - Singhvi, Shreyans D.; Singh, Preksha T. (International Journal of Research in Medical Sciences, 2020)
Background: Formaldehyde has been used as embalming fluid for cadavers’ in various medical colleges since decades, often alone but sometimes also with methyl alcohol, thymol crystals, glycerin and water. During dissection hours (average 6 hours per week), formaldehyde being an irritant can cause severe allergic responses in students of first year. Majorly the allergic symptoms are related to eyes, respiratory tract and skin. Methods: A case control study of 400 MBBS students was performed in Gujarat from April 2017-June 2017. The study included 200 case students who had been exposed to formaldehyde on 3 days of the week during anatomy dissection hours, also 200 final year students who were not exposed to formaldehyde regularly. Results: In our study, we have found the following positive responses to formaldehyde- general discomfort, sneezing, redness of eyes, itching of nostrils, irritation and itching of eyes, tears, blurring of vision, discharge from nostrils, and itching of skin while the following factors were found negative-vomiting, giddiness, drowsiness, nausea and difficulty in breathing. Conclusions: As, formaldehyde is commonly used and students are frequently exposed to it, it can be a cause of major concern and an alternative less toxic solution for embalming should be researched for.